THE INFLUENCE OF PLANNED BEHAVIOUR THEORY AND KNOWLEDGE TOWARDS THE WAQIF INTENTION IN CONTRIBUTING WAQF - Alifiandy, Mochammad Maulana; Sukmana, Raditya (Universitas Airlangga, 2020)
Waqf performance, as part of Islamic social finance is determined by, among others, willingness of society to donate their assets into waqf. Ability to understand determinants of the willingness may contribute to more optimum waqf assets accumulation and management. This study aims to investigate the effect of attitudes, subjective norms, perceived behavioral control, and knowledge in influencing the willingness of waqif to donate through the Airlangga University Social Fund Management Center (PUSPAS). This research is a quantitative study using multiple regression analysis. Data for this study is obtained from 98 respondents. The study results imply that there was no significant simultaneous influence in the variables of attitudes, subjective norms, behavioral control, and knowledge of waqif willingness to represent in PUSPAS. The attitude and knowledge variables are variables that have a significant influence partially. In contrast, the subjective norm variables and behavioral control have a partially insignificant impact on the intention of waqf to represent.